Amino acids, peptides and proteins. - Davies, J. S. (John Salmon), 1940- (Specialist periodical report., 2000)
In an ever-increasing domain of activity Amino Acids Peptides and Proteins provides an annual compilation of the world's research effort into this important area of biological chemistry. Volume 31 provides a review of literature published during 1998. Comprising a comprehensive review of significant developments at this biology/chemistry interface each volume opens with an overview of amino acids and their applications. Work on peptides is reviewed over several chapters ranging from current trends in their synthesis and conformational and structural analysis to peptidomimetics and the discovery of peptide-related molecules in nature. The application of advanced techniques in structural elucidation is incorporated into all chapters whilst periodic chapters on metal complexes of amino acids, peptides and beta-lactams extend the scope of coverage. Efficient searching of specialist topics is facilitated by the sub-division of chapters into discrete subject areas allowing annual trends to be monitored. All researchers in the pharmaceutical and allied industries and at the biology/chemistry interface in academia will find this an indispensable reference source.